Cheese rheology and texture - Gunasekaran, Sundaram, 1957- (CRC Press, Taylor & Francis Group, 2025)
"This comprehensive resource begins with an overview of cheesemaking technology and detailed descriptions of fundamental rheological test methods. It then presents uniaxial testing and fracture mechanics, the theory and applications of linear viscoelastic methods (dynamic testing), and the nonlinear viscoelasticity of cheeses. The book focuses on mechanics in its examination of cheese texture, while emphasizing measurement methods in its discussion of cheese meltability and stretchability. Finally, it addresses the effects of various factors, such as the composition and properties of milk, cheesemaking procedures, and post-manufacturing processes on the structure of cheese and the impact on functional properties"-- Provided by publisher.
Keywords: Cheese -- Texture.; elektronické knihy; electronic books